Pengaruh Stereotip Gender terhadap Persepsi Maskulinitas Penggunaan Skincare Masyarakat di Pulau Jawa - Oktarina, Arifa Azmi; Hadisiwi, Annisa; Ayumirza, Intania (CV. ITTC INDONESIA, 2025)
The development of technology and the entry of globalization into the line of people's lives in the modern era have caused a transformation in people's lifestyles. Skincare is one example of a cultural commodification product that has become an essential need for modern society. The perception of skincare as a woman's identity creates gender stereotypes that are inherent in community life, especially for the male community group who still tend to maintain conservative and patriarchal values. Skincare as a form of self-care is even considered against gender norms and prevailing masculinity values. Therefore, this study aims to see whether there is a significant influence of gender stereotypes on the perception of masculinity in the use of skincare products in urban communities on the island of Java using quantitative method. Primary data from this study were collected through a Likert Scale questionnaire from 100 respondents from different age categories, domiciles, and occupations to later be tested for validity, reliability, and hypothesis influence. The results of the study using the Regression test showed that the significance value (Sig.) of gender stereotypes (X) was <0.001, so that H0 which states that the regression coefficient = 0 is rejected and the X variable has a significant effect on the Y variable. Based on these results, it can be concluded that gender stereotypes play a role in shaping the perception of masculinity, including urban communities on the island of Java, in using skincare products by 48.1%.